FAKTOR-FAKTOR PENDORONG INDIVIDU MELAKUKAN BELANJA ONLINE - Tri Wahyuarini; Evi Sofiana; Syarifah Novieyana (Politeknik Negeri Bengkalis, 2019)
This research used Theory of Planned Behavior’s model to explain factors that caused people to do online shopping by adopting Limayem et al. (2000) research. Limayem’s study explain about factors that caused online shopping behavior especially intention to do online shopping which determined by perception of the consequences of behavior, attitude towards online shopping, personal innovation, subjective norms and control behavior.The main construct of this research also adopted Limayem’s study, namely : intention and behavior to do online shopping. Intention to do online shopping consist of five constructs which are attitude towards online shopping, subjective norms, personal innovation, perception of the consequences of behavior, and control behavior.The main purpose of this research is to examine whether attitude towards online shopping, subjective norms, personal innovation, perception of the consequences of behavior, and control behavior have a positive effect to intention to do online shopping and whether intention to do online shopping have a positive effect to online shopping behavior. Empirical hypothesis are used to proof the main purpose, by using correlation as the data testing tool.The result shows that the 1st hypothesis is proven, which means there is a positive effect of attitude towards online shopping, subjective norms, personal innovation, perception of the consequences of behavior, and control behavior to intention to do online shopping. It is show by signification number 0.000. The result from 2nd hypothesis is also proven, which confirm the positive effect intention to do online shopping with online shopping behavior. But one of the construct was dropped from the early data processing caused by unsatisfactorily validity.